The basis of state image formation in international communication, as exemplified by the Republic of Belarus - Zhminko, Elena (Politologia, 2020)
In the modern world, the formation of a state’s image, which is one of its main resources, largely depends on the state’s participation in international communication processes. Whether the formation of the image will be successful is largely determined by three factors: the clarity and intelligibility of its identification, both for its citizens and the international community; the compliance of the legal framework in the field of information relations with international standards; and the structuring of the information policy according to the principles of two-way communication, including openness and free access to information. The political authorities of the Republic of Belarus, relying on the concept of ideologization, treat the global exchange of information as a threat to the legitimacy of its power and try to cultivate absolute control over the communication and information processes, paradoxically making it impossible to implement the tasks set by themselves in this area.